2017
DOI: 10.3945/ajcn.116.134544
|View full text |Cite|
|
Sign up to set email alerts
|

Analytical ingredient content and variability of adult multivitamin/mineral products: national estimates for the Dietary Supplement Ingredient Database ,

Abstract: Background: Multivitamin/mineral products (MVMs) are the dietary supplements most commonly used by US adults. During manufacturing, some ingredients are added in amounts exceeding the label claims to compensate for expected losses during the shelf life. Establishing the health benefits and harms of MVMs requires accurate estimates of nutrient intake from MVMs based on measures of actual rather than labeled ingredient amounts. Objectives: Our goals were to determine relations between analytically measured and l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
40
0
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(47 citation statements)
references
References 40 publications
0
40
0
4
Order By: Relevance
“…As far as we know, no other studies have tested folic acid supplements for the presence of PABA-glu or PABA, but several studies have reported issues with the stability and dissolution of commercial folic acid supplements (Hoag et al, 1997;Sculthorpe et al, 2001). In light of these issues, manufacturers have adopted a policy of 'overages' in order to ensure sufficient folic acid is released in the small intestine following ingestion (Andrews et al, 2017). The presence of PABA-glu and PABA in a commercially available folic acid source (Figure 3) combined the instability of folic acid at the low pH conditions of the stomach, makes it likely that PABA-glu and PABA will be available to the gut microbiota following supplementation.…”
Section: Discussionmentioning
confidence: 99%
“…As far as we know, no other studies have tested folic acid supplements for the presence of PABA-glu or PABA, but several studies have reported issues with the stability and dissolution of commercial folic acid supplements (Hoag et al, 1997;Sculthorpe et al, 2001). In light of these issues, manufacturers have adopted a policy of 'overages' in order to ensure sufficient folic acid is released in the small intestine following ingestion (Andrews et al, 2017). The presence of PABA-glu and PABA in a commercially available folic acid source (Figure 3) combined the instability of folic acid at the low pH conditions of the stomach, makes it likely that PABA-glu and PABA will be available to the gut microbiota following supplementation.…”
Section: Discussionmentioning
confidence: 99%
“…Infusion of [ 3 H] PABA into the colon of rats [67] and piglets [68] could be traced to THFs in the host, demonstrating that bacterial uptake of PABA generates THFs that are absorbed and used in one-carbon metabolism. The lack of regulation of micronutrient supplements but fierce competition on the market has led to a compromise on quality, and folic acid supplements are commonly found to fail tests of stability and dissolution [69][70][71][72]. Combined with the instability of folic acid at low pH [73], it is likely that folic acid breakdown products will be available to the colonic microbiota following long-term supplementation.…”
Section: Folic Acidmentioning
confidence: 99%
“…Specific research needs to guide the interpretation of data on program exposure and excessive intake include (1) reevaluation of the ULs, including collection of new data on functional outcomes linked to excessive intake; (2) identification and characterization of biomarkers of MN excess, along with thresholds to indicate increasing risk of toxicity; (3) simplification of dietary intake data collection and analysis, with attention to cataloging the nutrient content of supplements and fortified processed foods; (4) improved tools for estimating the effects of existing and alternative intervention programs on benefits and risks, with special attention paid to intervention program costs; and (5) methods for combining information on deficiency and excess and utilizing this information in policy discussions.…”
Section: Suggested Program Indicators and Data Collection Mechanismsmentioning
confidence: 99%